Photoelectrocatalytic oxidation of As(III) over hematite photoanodes: A sensible indicator of the presence of highly reactive surface sites. (1st December 2018) - Spanu, Davide; Dal Santo, Vladimiro; Malara, Francesco; Naldoni, Alberto; Turolla, Andrea; Antonelli, Manuela; Dossi, Carlo; Marelli, Marcello; Altomare, Marco; Schmuki, Patrik; Recchia, Sandro
Abstract: Hematite-based photoanodes were used for the photoelectrocatalysed batch oxidation of As(III) in water at pH 7 and 10. Tests were carried out at different As(III) initial concentrations, ranging from 150 μg/L to 30 mg/L. With no pre-treatments, an initial inactive period of 40–50 min was always observed at the beginning of every test. This initial inactive period is completely removed by a surface modification of surface active sites induced by a pre-polarisation at 800 mV (vs. Ag/AgCl). The water splitting active sites related to the Fe(III)-Fe(IV) redox couple were proved to be not active towards As(III) oxidation. The modifications induced by the anodic prepolarisation were deeply studied: no evidence of the formation of surface highly oxidised iron sites (Fe(V) or Fe(VI)) and/or of highly reactive oxygen vacant sites emerges from XPS analysis. Rather, all collected characterisation data support the conclusion that more reactive terminal oxygen species are necessary for As(III) oxydation. The As(III) abatement reaction was modelled by two subsequent first order kinetics in As(III), independently from the initial As(III) concentration: this behaviour was explained suggesting that the highly reactive sites, being formed after prepolarisation, are gradually depleted during the reaction. As this reaction was proved to be very sensitive to the presence of highly reactive iron sites, its utilisation as a probe reaction to study hematite photoanodes is suggested. Graphical abstract: Highlights: Hematite photoanodes catalyse the oxidation of As(III) under solar illumination. Up to 90% As(III) abatements are observed within 24 h independently from the initial As(III) concentration. The proposed process is in principle environmentally sustainable, as the disposal of chemicals is almost totally absent. The production of hydrogen during As(III) oxidation provides a suitable power source to sustainably drive the process.